Substitute child care as a current problem of social care in the Czech Republic - Viera Vavrecková; Michaela Tichá; Zlata Ondrúšová (DANUBE: Law, Economics and Social Issues Review, 2017)
In the event of the breakdown of the original family, institutional care has for many decades been the preferred alternative to family substitute care or aid to the original family. The origins of this practice can be traced to the 1950s, when foster families were cancelled by the communist regime and the ideology of collective upbringing triumphed. The objective of this essay is to determine how substitute child care in the Czech Republic has changed in the last ten years. The unfortunate practice of giving preference to institutional care in the event of the breakdown of the original family is changing: between the years 2005-2016 the number of children in institutional facilities for the youngest children (up to three years of age) has decreased by 30%; a similar trend may be observed in older children assigned to institutional or protective care. In contrast, the number of children in foster care has increased by 2.5 times since 2004. In 2016 40% more children lived in all forms of formal family substitute care compared to 2009. The problem remains the fragmented nature of legislation among the various ministries and the inadequate support of families in danger of social exclusion. A disproportionate number of children continue to be placed in substitute care due to non-existent public housing and inadequate networks of outpatient, field, and support services.
Keywords: 330; Social Work; Social/Legal Child Protective Services; Institutional Care; Family Substitute Care; Foster Care